2007
DOI: 10.1177/000313480707300101
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion is an Independent Predictor of Mortality after Blunt Trauma

Abstract: Allogeneic blood transfusion is associated with increased morbidity and mortality. The authors evaluated the affect of blood transfusion, independent of injury severity on mortality. The authors conducted a retrospective review of all patients, age ≥18 years with blunt injury admitted to their Level 2 trauma center from 1994 to 2004 by query of the NTRACS trauma registry. Initial systolic blood pressure and heart rate determined the shock index. Logistic regression was used to model the affect of blood transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Following the first week after injury, despite having gained control of bleeding, patients continue to be transfused on average one to two units of packed red blood cells per week, and this has been linked with immune suppression, infectious complications, and increased mortality. [4][5][6] While an acute anemia is diagnosed in the majority of trauma patients admitted to the ICU, anemia has been found to persist for the duration of their critical illness and can last for weeks to months following the initial injury. 2,7 Other than treatment with blood transfusions, persistent injuryassociated anemia has largely been refractory to exogenous erythropoietin (EPO) administration and iron supplementation or transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first week after injury, despite having gained control of bleeding, patients continue to be transfused on average one to two units of packed red blood cells per week, and this has been linked with immune suppression, infectious complications, and increased mortality. [4][5][6] While an acute anemia is diagnosed in the majority of trauma patients admitted to the ICU, anemia has been found to persist for the duration of their critical illness and can last for weeks to months following the initial injury. 2,7 Other than treatment with blood transfusions, persistent injuryassociated anemia has largely been refractory to exogenous erythropoietin (EPO) administration and iron supplementation or transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma patients with an ISS of 75 are often described as the most severe injuries with the lowest possible survival rate among trauma researchers. In several studies [36,37] researchers excluded this type of patients. But Peng et.…”
Section: The De Nition Of Cervical Spinal Cord Injury Is Based On Thementioning
confidence: 99%
“…3,4 Peri-operative allogeneic blood transfusion increases the risk of postoperative infection and transfusion reactions which may slow post-operative recovery. [5][6][7] Randomised clinical trials have shown that using a gelatine matrix with thrombin to assist haemostasis decreases the operating time and intra-operative blood loss of patients undergoing cardiac, 8 general, 9,10 and ENT surgery. 11,12 There are, however, few randomised clinical trials on its use in orthopaedic or spinal surgery.…”
Section: Cite This Article: Bone Joint J 2016;98-b:395-401mentioning
confidence: 99%